K-9 Alaskan defense - Varland, Sarah (K-9 search + rescue., 2025)
"Discovering a dead body in the woods turns into a fight for survival when Lily Peterson is attacked by an unknown assailant. Rescued by her retired police K-9, Timber, Lily calls the one man she trusts for help--her late fiancé's partner, former officer Travis Beckett. Only, the danger proves to be far from over when Lily's house goes up in flames. Someone wants her dead, and all clues lead to a connection to her departed fiancé's final case. Investigating the past is the only way to stay alive...but can they elude a killer neither expects?" -- Page [4] cover.